PENGARUH PERHATIAN ORANG TUA DAN MOTIVASI BERPRESTASI TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN PEMELIHARAAN KELISTRIKAN KENDARAAN RINGAN KELAS XII DI SMKN 1 NGAWEN - ACHMAD ZUNAIDI (Universitas Negeri Yogyakarta, 2021)
This study aims to: (1) determine the effect of parents attention on learning achievement; (2) Knowing the effect of achievement motivation on learning achievement; (3) Knowing the effect of parents attention and achievement motivation on the learning achievement of class XII student in the Light Vehicle Electrical Maintenance subject at SMK Negeri 1 Ngawen. The research carried out was ex post facto research. The place of this research is at SMK Negeri 1 Ngawen and the time of the research was conducted in the 2020/2021 academic year. The sample of this research is students of class XII TKR C in the subject of Light Vehicle Electrical Maintenance. The data collection technique is done by observation and questionnaires. The data used is quantitative data. The validity of the data was obtained through validity and reliability. The results of this study indicate that (1) Parents' attention have a significant effect on the Light Vehicle Electrical Maintenance Learning Achievement of Class XII TKR Students at SMK Negeri 1 Ngawen for the 2020/2021 academic year as seen from the value of tcount = 3.459 with a significance value of 0.002, (2) Achievement motivation does not have a significant effect on the Learning Achievement of Electrical Light Vehicle Maintenance for Class XII TKR Students of SMK Negeri 1 Ngawen 2020/2021 academic year which is seen from the value of tcount = 0.245 with a significance value of 0.808.Keywords: parents attention, achievement motivation, learning achievement